KNOWLEDGE, ATTITUDE AND PRACTICE ON STERILIZATION AMONG DENTAL COLLEGE STUDENTS - A SURVEY (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Sterilization refers to the process of removing any kinds of microorganisms such as fungi, bacteria and spores or other biological agents like prions present in the surface or objects. Any surgical instruments that penetrate our bloodstream or skin must be sterilized before using and examples of these instruments are pacemakers and needles. There are different types of sterilization methods like physical and chemical sterilization in which heat, incineration and flaming comes under physical type and ethylene oxide, formaldehyde and hydrogen peroxide comes under chemical type of sterilization . Some of the advantages of sterilization methods are destruction of bacterial spores and it is the most cheap and economical method .Aim: The aim of this study is to determine the knowledge, attitude and practice on sterilisation protocols among dental college students.Materials and Methods: A well structured questionnaire containing socio-demographic information, knowledge, attitude and perception was framed and circulated through google forms survey link. The results were imported to excel and were statistically analysed using IBM SPSS software v.26. Results and Discussion: The results conclude that awareness on sterilization protocols was good among dental college students and further studies can be done for more awareness in a different and large population. From the data, chi square value was obtained by comparing gender of the participants in which p value <0.05 is statistically significant.Conclusion: In this study, the students had knowledge and sufficient awareness about the sterilization protocols. The students were exposed for the methods of sterilization and also they knew the types of sterilization methods. Therefore, from this study, we conclude that dental college students were aware of sterilization protocols.